2008
DOI: 10.1080/00048670701827291
|View full text |Cite
|
Sign up to set email alerts
|

Many Faces of the Dual-Role Dilemma in Psychiatric Ethics

Abstract: In psychiatric ethics, the dual-role dilemma refers to the tension between psychiatrists' obligations of beneficence towards their patients, and conflicting obligations to the community, third parties, other health-care workers, or the pursuit of knowledge in the field. These conflicting obligations transcend a conflict of interest in that the expectations of the psychiatrist, other than the patient's best interests, are so compelling. This tension illustrates how the discourse in psychiatric ethics is embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 67 publications
0
26
0
2
Order By: Relevance
“…This dual role can cause dilemmas for the practitioner who has potentially incompatible duties to the patient, third parties and the wider community [1][2][3]. As Robertson and Walter [4] observed: ''In psychiatric ethics, the dual-role dilemma refers to the tension between psychiatrists' obligations of beneficence towards their patients, and conflicting obligations to the community, third parties, other healthcare workers, or the pursuit of knowledge in the field''. They noted further that these conflicting obligations create a conflict of interest because the expectations of psychiatrists, aside from those related to the best interest of the patients, are quite ''compelling''.…”
Section: Introduction Forensic Psychiatrymentioning
confidence: 99%
“…This dual role can cause dilemmas for the practitioner who has potentially incompatible duties to the patient, third parties and the wider community [1][2][3]. As Robertson and Walter [4] observed: ''In psychiatric ethics, the dual-role dilemma refers to the tension between psychiatrists' obligations of beneficence towards their patients, and conflicting obligations to the community, third parties, other healthcare workers, or the pursuit of knowledge in the field''. They noted further that these conflicting obligations create a conflict of interest because the expectations of psychiatrists, aside from those related to the best interest of the patients, are quite ''compelling''.…”
Section: Introduction Forensic Psychiatrymentioning
confidence: 99%
“…It refers to psychiatrists' conflicting obligations to their patients and to a powerful third party. Nevertheless, although the moral tensions implicit in a dual role (Austin, 2008;Robertson, 2008) form one important aspect of the present study, in contrast to the more traditional psychiatry within NAA such tensions are not seen as phenomena to be avoided.…”
Section: In a Jungle Of Voicesmentioning
confidence: 79%
“…The interviewees utilized the interviews as a form of clinical supervision, and those who had an ongoing therapeutic relationship with the clients planned changes to the treatments. The diverse barriers to agency resulted partly from the dual-role dilemma (Robertson, 2008), with psychiatrists finding themselves to be servants of several masters. The strength of institutional forces seen in the study was also found in a study by Austin (2008): actions became agent-less, which was experienced as morally disturbing by the psychiatrists.…”
Section: Discussionmentioning
confidence: 99%
“…The expert consensus indicated the importance of an MDT in the performance of the psychiatric examination. Since there may be a risk of a dual-role dilemma between the evaluator and the therapist if the examiner and the physician in charge are the same person [13], the examiner must not be the physician in charge of the subject [8]. However, this principle is not well known to forensic psychiatrists in Japan.…”
Section: Discussionmentioning
confidence: 99%